Alcoholic Beverage Preference and Dietary Habits: A Systematic Literature Review. Issue 14 (25th October 2016) - Sluik, Diewertje; Bezemer, Rianne; Sierksma, Aafje; Feskens, Edith
Abstract : Introduction : The aim of this review is to systematically and critically evaluate the existing literature into the association between alcoholic beverage preference and dietary habits in adults. Methods : A literature search was conducted in the databases of Medline (PubMed), ISI Web of Knowledge, and PsycINFO for studies published up to March 2013. From a total of 4, 345 unique hits, 16 articles were included in this systematic review. Two independent reviewers extracted relevant data for each study and assessed study quality. Results : 14 cross-sectional and two ecological studies from the United States and several European countries were included. Across different study populations and countries, persons with a beer preference displayed in general less healthy dietary habits. A preference for wine was strongly associated with healthier dietary habits in Western study populations, whereas studies in Mediterranean populations did not observe this. Dietary habits of persons with another preference or who were abstinent were less reported. Conclusion : This review has shown that the preference for a specific alcoholic beverage is associated with diet. Thus, it might not be the alcoholic beverage but the underlying dietary patterns that are related to health outcomes.